Adaptation and Innovation An Analysis of Crop Biotechnology Patent Data - Agrawala, Shardul (OECD Environment Working Papers, 2012)
Innovation in technologies that promote mitigation and adaptation will be critical for tackling climate change. It can decrease the costs of policy measures and provide new opportunities for the private sector. However, most discussions of innovation have focused on mitigation, while little attention has been paid to innovation for adaptation. This paper uses agricultural crop biotechnology as a case study of innovative activity. The agricultural sector is considered to be particularly vulnerable to climate change, in addition to facing the pressures of meeting the demands of a rising world population. Innovation in plant breeding to develop crop varieties that are more resilient to climate change impacts is one of several possible adaptation options for agriculture. This paper neither advocates nor discourages the use of biotechnology, but focuses on providing estimates of the level and trends of innovation in this field